Grandparents in Strengthening Children’s Spiritual Intelligence in Mlaten Village, Mijen District, Demak Regency - MUBAROK, M. ALI (Tasamuh: Jurnal Studi Islam, 2023)
Abstract: Grandparenting is childcare carried out by surrogate parents (grandparents) where grandparents are part of a large family that is trusted by parents to care for their children either temporarily or permanently, in their care grandparents educate their grandchildren in the ability to strengthen spiritual intelligence which is covering a wide variety. This study uses qualitative field research, where data is obtained through interviews. The results of the study stated that the background of the occurrence of grandparents was due to various things: infidelity, divorce, or being left by their parents to work. Then grandparents in strengthening children's spiritual intelligence by familiarizing themselves with religious activities such as: learning the Koran, praying in congregation, and training themselves to be honest in all things. Then the impact of grandparents is being able to strengthen religious traits in everyday life such as worship activities, socializing well, and being able to distinguish between good and bad traits. Keywords: Grandparenting, Spiritual Intelligence, Children